1988
DOI: 10.1525/aa.1988.90.4.02a00060
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Polygyny: Ecology, Economy, Kinship, and Warfare

Abstract: We discuss and test competing explanations for polygyny based on household economics, malecentered kin groups, warfare, and environmental characteristics. Data consist of codes for 142 societies from the Standard Cross-Cultural Sample, including new codes for polygyny and environmental characteristics. An explanatory model is testedfor the worldwide sample using regression analysis, and then replicated with regional samples. We obtain conuergent results with two different measures of p o & . n y , cultural rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(103 citation statements)
references
References 33 publications
2
99
1
1
Order By: Relevance
“…One of the most important of these mores is the prohibition against polygynous marriages (Alexander, 1979;MacDonald, 1995;White & Burton, 1988). In societies in which polygyny is not constrained, culturally successful men (about 10-15% of men) will typically marry several women (Murdock, 1981).…”
Section: Cultural Mores and Resource Availabilitymentioning
confidence: 99%
“…One of the most important of these mores is the prohibition against polygynous marriages (Alexander, 1979;MacDonald, 1995;White & Burton, 1988). In societies in which polygyny is not constrained, culturally successful men (about 10-15% of men) will typically marry several women (Murdock, 1981).…”
Section: Cultural Mores and Resource Availabilitymentioning
confidence: 99%
“…This study also found that Yorubas had the highest proportion of men who knew exact menstrual cycle dates of their wives ( Table 2). The polygamous nature commonly found with the Yorubas and Hausa clans could be barriers for intimate communication between husbands and wives 26 . Furthermore, an infamous notion by husbands thinking that discussions around family planning and female reproductive health with wives is a dent on their manhood 27 may also be a plausible reason for this lackadaisical attitude.…”
Section: Discussionmentioning
confidence: 99%
“…Since most of the societies in the Karamojong-Kipsikiis clade lie in closer vicinity to each other than to the societies with rare polygyny (Murle, Acholi, and others), it is quite plausible that polygyny is transmitted between neighbors, particularly in contexts in which fraternal interest groups raid cattle from surrounding ethnic groups in order to acquire the bridewealth for multiple marriages or to settle new territory. 80 In reality, the truth probably lies somewhere in between, with rates of polygyny varying both in response to socioecological conditions 99 and reflecting an ancestral tradition. 61 It is worth adding a point to which we will return, that horizontal transmission is much more likely to occur and to be detected in fine-grained regional studies such as this, where the mean and maximum distances between populations are about 300 and 1100 km, respectively, than in, for example, a pan-African study where the equivalent figures are approximately 3,000 and 8,000 km.…”
Section: Do Cultural Traits Show Evidence Of Horizontal Transmission?mentioning
confidence: 99%
“…Are they cattle or wife raiders, what is their population density, and do they have a shortage of agricultural land? 80 Conversely, neighboring populations are perhaps less likely to adopt an entire inheritance system, shifting from patriliny to matriliny as a result of the behavior of their neighbors. 81 Finally it is quite possible that a specific trait may show vertical transmission in one context and horizontal transmission in another.…”
Section: Remaining Challenges In Untangling Transmission Patternsmentioning
confidence: 99%